'It needs a complete overhaul…' district manager perspectives on the capacity of the health system to support the delivery of emergency obstetric care in an urban South African district. Issue 1 (1st January 2019) - Thwala, Siphiwe Bridget Pearl; Blaauw, Duane; Ssengooba, Freddy
ABSTRACT: Background : A high maternal mortality ratio persists in South Africa despite developments in emergency obstetric care (EmOC), a known effective intervention against direct causes of maternal deaths. Strengthening the health systems is one of the focus areas identified by the National Committee for Confidential Enquiries into Maternal Deaths in South Africa. District managers as immediate overseers of the frontline health system are uniquely positioned to provide insight into the overall health system processes that influence the delivery of EmOC. Objective : We sought to identify health system enablers and barriers to the delivery EmOC from the perspective of district managers. This would potentially unearth aspects of the health system that require strengthening to better support EmOC and improve maternal outcomes. Methods : Face-to-face audio-recorded key informant interviews were conducted with 19 district managers in charge of the delivery of EmOC in one urban district. Interviews were transcribed and coded. Related codes were inductively grouped into emerging themes. Deductive thematic analysis was then applied to categorise emergent themes into the WHO health system building blocks. Results : Themes included a weaknesses in the organisation of health services; a high vacancy and turnover of senior management; poor clinical accountability from EmOC providers; inadequate resources (including infrastructure, staffing, and funding); and the need to improve district health information system indicators. Conclusion : The functioning of the district health system was weak, affecting the delivery of EmOC. Unless staffing is effectively addressed, the health system is unlikely to reduce maternal mortality to the desired level. Coordination of EmOC services by managers needs to be strengthened to limit fragmentation of care and improve the continuity EmOC. Furthermore, a high turnover of senior leadership affects implementation priorities and continuity in the overall strategic direction of EmOC.